Images performed by words in Howard Jacobson’n novel Kalooki Nights. Remarks about intersemiotic relations among words and pictures - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Images performed by words in Howard Jacobson’s novel “Kalooki Nights”. Remarks about intersemiotic relations among words and pictures The article titled Images performed by words in Howard Jacobson’n novel Kalooki Nights. Remarks about intersemiotic relations among words and pictures concerns the intersemiotic tensions among words and pictures. The theoretical model is supported by the interpretation of Howard Jacobson’s novel titled Kalooki Nights. This novel redefines the limits of representation and reception of the Holocaust in the context of identity and contemporary world. Exploring the forms of “reading” (“looking at”) of the linguistic codes as the visual codes, such terms like “transframing” and “performing” refer to the patterns of creation the fictional worlds (constructed by the words which are treated as the images). The being of words still means looking through them, through their semantic flaws. This intersemiotic translations are rooted in the will of creation (Eros) and the will of destruction (Thanatos). The history of interpretations of these two sources of semiosphere touches the limits of questions: what can be shown in written wor(l).